2014
DOI: 10.1039/c4ra07345b
|View full text |Cite
|
Sign up to set email alerts
|

Photo-responsive reversible micelles based on azobenzene-modified poly(carbonate)s via azide–alkyne click chemistry

Abstract: We provide a convenient method to construct photo-responsive poly(carbonate)s via ring-opening polymerization of cyclic carbonates followed by azide–alkyne click chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…1,8‐Diazabicyclo[5.4.0] undec‐7‐ene (DBU) and 2‐chloro‐ N , N ‐diethylethylamine hydrochloride were bought from Energy Chemical. 4‐(4‐Azidebutyloxy)−4'‐trifluoromethoxy‐azobenzene (Azo‐N 3 ) was prepared as reported previously . All other reagents and solvents were purchased from Sinopharm Chemical Reagent, China and used as received.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,8‐Diazabicyclo[5.4.0] undec‐7‐ene (DBU) and 2‐chloro‐ N , N ‐diethylethylamine hydrochloride were bought from Energy Chemical. 4‐(4‐Azidebutyloxy)−4'‐trifluoromethoxy‐azobenzene (Azo‐N 3 ) was prepared as reported previously . All other reagents and solvents were purchased from Sinopharm Chemical Reagent, China and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…However, limited reports regarding the synthesis of light‐responsive poly(carbonate)s based on Azo have been explored. We have previously developed a type of photo‐induced reversible poly(carbonate)s PMPC‐Azo by covalent binding of the Azo photochromic moieties to the main chain . But polymeric nanoparticles just dealing with response to single stimulus were not sufficient enough to meet the need of triggering drug release in tumor tissues exactly.…”
Section: Introductionmentioning
confidence: 99%
“…By exploiting ring‐opening polymerization (ROP) and alkyne–azide click reaction, Lu et al reported a nanoscale polymer micelle based on PEO‐modified amphiphilic polycarbonate with AZO side chains (PTMC‐azo) for drug delivery ( Figure a) . The polymer micelles were formed by mixing copolymer within aqueous solution, allowed hydrophobic drugs (NR as the model drug) in the hydrophobic core.…”
Section: Uv/vis Light Controlled Drug Delivery Systemsmentioning
confidence: 99%
“…UV–vis spectra of the PTMC‐azo micelles upon irradiation with b) 365 nm UV light for the drug release and with c) 450 nm visible light for the drug re‐encapsulation. Reproduced with permission . Copyright 2014, Royal Society of Chemistry.…”
Section: Uv/vis Light Controlled Drug Delivery Systemsmentioning
confidence: 99%
“…Wang et al [20,21], and Jochum and Theato [22] used this reversible polarity shift to fabricate micellar systems that could be disrupted and reformed by controlling UV and visible light illumination. Hu et al [23] demonstrated encapsulation of the model drug Nile Red and the photoresponsive release and re-encapsulation behaviors of amphiphilic azobenzene-modified copolymers with low cell cytotoxicity. There are several other reports on synthesis and function of photoresponsive amphiphilic polymers that are based on the isomerization of azobenzene [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 98%